Effects of particle sizes on gas-solid flow and gas production in fluidized-bed gasification of brewer’s spent grains based on CPFD simulations - Hongshuai GUO; Huawei JIANG; Hairui YANG; Cuiping WANG; Yanhui LI (Meitan xuebao)
A large number of waste brewer’s spent grains (BSGs) have been produced every year in brewing industry of China, which have the advantages of high volatile matter content and low sulfur content, especially suitable for being utilized as gasification raw materials. Fluidized-bed gasifiers are famous for their excellent gas-solid mixing and temperature uniformity. Therefore, it is of great significance to realize the resource use and energy utilization of BSGs by fluidized-bed gasification. In order to investigate the effects of particle sizes on gas-solid flow behavior and gas production in the fluidized-bed gasification of BSGs, the numerical simulations of the gasification of BSGs in a bubbling fluidized-bed gasifier with air and water vapor as gasification agents were performed, based on computational particle fluid dynamics (CPFD) method. The effects of bed-materials particle sizes and BSGs particle sizes were both studied. The distribution of particle volume fraction, the particle distributions of BSGs and bed materials, and the mole fractions of main gas components were obtained by the CPFD numerical simulation. An experimental apparatus for bubbling fluidized-bed gasification was used to study the effects of bed-materials particle sizes and BSGs particle sizes on the volume fractions of main gas components in the product gas, which validated the numerical simulation results. The results showed that the increases of bed-materials particle sizes were not conductive to adequate fluidization and particle mixing, which made the temperature distribution uneven along the height. The increases of bed-materials particle sizes were also not conductive to the intensive mixing of carbon particles and water vapor, and the uniform heat absorption or heat release of gas-solid reaction and gas-phase reaction, resulting in a significant reduction of H2 mole fraction. The appropriate increases of BSGs particle sizes helped to prolong their residence time in the gasifier, thus improving the reaction conversion rate between solid carbon and water vapor or carbon dioxide, and generating more H2 and CO. However, excessive large BSGs particle sizes caused the poor mixing of BSGs and bed materials, which reduced the specific surface areas of BSGs, and were not conducive to the pyrolysis and gasification reaction, leading to the reduction of the molar fractions of combustible components such as H2, CO, CH4 and NH3.